The Location of the Philippines within Spanish Official Frameworks - Díaz Rodríguez JM (Edizioni Ca' Foscari, 2019)
This article explores several notions of location in relation to the Philippines. Contrasting Filipino studies which problematise conceptions of the Philippines as Asian, this essay focuses on Spanish perceptions of the archipelago in official political and economic plans regarding Spain’s presence in Asia in the 21st century. The Philippines plays an important role in these plans, as it is listed as a priority country for Spanish actions in this region, mostly due to the shared colonial links. Despite this shared history, there are several Spanish ambivalent perceptions that locate the Philippines as a country connected to Spain and, at the same time, in the periphery of countries with a Hispanic heritage, which is evident in the location of Fil-Hispanic studies within Hispanic scholarship. Furthermore, Spanish official perceptions are often politically motivated, in relation to the practical uses that the location of the Philippines can have for Spain as a gateway to Asia, in particular, the neoliberal focus of certain Spanish policies, which re-establish a centre-periphery dynamics in a neo-colonial global context.